Tetrahydropyrazolo[1,5-a]pyridine-fused steroids and their in vitro biological evaluation in prostate cancer - Jorda, Radek (2019)
S.M.M.L., A.V.P. and T.M.V.D.P.eM. thank Coimbra Chemistry Centre (CQC) , supported by the Portuguese Agency for Scientific Research , “Fundação para a Ciência e a Tecnologia” ( FCT ), through project UID/QUI/00313/2019 . We also acknowledge the UC-NMR facility for obtaining the NMR data ( www.nmrccc.uc.pt ). C.S.B.G. acknowledges the Associate Laboratory for Green Chemistry-LAQV which is financed by national funds from FCT/MCTES ( UID/QUI/50006/2019 ). The authors (RJ, EŘ) wish to acknowledge the support from the European Regional Development Fund (Project ENOCH, No. CZ.02.1.01/0.0/0.0/16_019/0000868) and Palacký University in Olomouc ( IGA_PrF_2019_013 ).